Efficacy of Intralesional Methotrexate Injection versus Triamcinolone Acetonide in Nail Psoriasis: A-Systematic Review and Meta-Analysis - Stephanie Nathania; Diah Adriani Malik; Muslimin; Hardian (Mattioli1885, 2024)
Introducion: Psoriasis is a chronic inflammatory skin disease that can affect many parts of the body. Psoriatic involvement of the nail bed or nail matrix results in nail psoriasis that is common. Patients with psoriatic nails have impaired quality of life due to the appearance of nails, and significant morbidity and functional impairments may arise in large cases. The management of nail psoriasis is challenging because it is usually time-consuming with unsure outcomes. The existing evidences suggest that intralesional injection are particularly effective for nail psoriasis. Current studies provide recommendations on the intralesional injection technique, recommending an optimal concentration of methotrexate (MTX), triamcinolone acetonide (TA), and cyclosporine but the comparison of these treatment was still limited. Objective: This study aimed to evaluate the efficacy of intralesional injections of MTX compared with TA in treating nail psoriasis using Nail Psoriasis Severity Index (NAPSI) score. Methods: A systematic literature search was performed using EBSCOhost, Scopus, ProQuest, ScienceDirect, SpringerLink, Elsevier Clinical Key, Cochrane library, ClinicalTrials.gov subgroups terms: "intralesional methotrexate injections for nail psoriasis", "intralesional triamcinolone acetonide injections for nail psoriasis" and "NAPSI Score". Three studies were included in the qualitative synthesis and meta-analysis. Results: The overall SMD in NAPSI scores after administration of intralesional injection of MTX and TA was -0.213±0.232 (95% CI = -0.667 to 0.241). The Q statistic value was -0.921 (p=0.357), indicating the insignificant difference in the effectiveness of both therapies. Conclusion: Both MTX and TA were effective in treating nail psoriasis based on the reduction of NAPSI score.